2017
DOI: 10.1002/bmc.3909
|View full text |Cite
|
Sign up to set email alerts
|

Relative tissue distribution and excretion studies of gastrodin and parishin from powder and extract of Gastrodiae Rhizoma in rat by UHPLC‐ESI‐MS/MS

Abstract: New research has indicated that Gastrodiae Rhizome (GR) has potential anti-diabetic and anti-asthmatic effects in mouse models. On the basis of our previous study of the relative bioavailability of gastrodin (GAS) and parishin (PA) from extract and powder of GR, we performed further research on the tissue distribution and excretion of the two analytes. A reliable bioanalytical method for the quantification of GAS and PA in rat tissues and excretion is required. Chromatographic separation was carried out on a g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 34 publications
1
5
0
Order By: Relevance
“…These correlation coefficients ( Figure 3 ) suggest that gastrodin and parishin compounds can be biotransformed into each other at different rates in vivo. This finding is consistent with previous reports of biotransformation between parishins and gastrodin [ 4 ], furthermore, our detected compounds were also reported by Tang et al [ 25 ] using the Q-TOF-MS/MS.…”
Section: Resultssupporting
confidence: 94%
“…These correlation coefficients ( Figure 3 ) suggest that gastrodin and parishin compounds can be biotransformed into each other at different rates in vivo. This finding is consistent with previous reports of biotransformation between parishins and gastrodin [ 4 ], furthermore, our detected compounds were also reported by Tang et al [ 25 ] using the Q-TOF-MS/MS.…”
Section: Resultssupporting
confidence: 94%
“…Jiang et al measured the distribution and excretion of Gas in the heart, liver, spleen, lung, kidney, brain, and urine of rats. The results showed that the distribution of Gas can be detected in the kidney, liver, and lung, but not in the brain [ 119 ]. It is speculated that Gas failed to penetrate the BBB.…”
Section: Chinese Herbal Monomersmentioning
confidence: 99%
“…Jia et al identified four metabolites of methyl-d-glucoside, p-hydroxybenzenesulfonic acid, p-methyl-d-glucoside, and p-hydroxy benzaldehyde in rat plasma for the first time [ 122 ]. Tang [ 123 ], Jiang [ 119 ], and Liu [ 124 ] studies have shown that parishin can be metabolized into Gas in vivo. Furthermore, the direction of intestinal microorganisms is also related to the study of drug metabolism.…”
Section: Chinese Herbal Monomersmentioning
confidence: 99%
See 1 more Smart Citation
“…Validation of the pharmacokinetic method was according to the FDA guidelines, including selectivity, linearity, precision, accuracy, matrix effects, extraction recovery, and stability [ 20 ].…”
Section: Methodsmentioning
confidence: 99%